PROPOSAL FOR A SHARED CLASSIFICATORY TREE FOR DOBES LANGUAGE DOCUMENTATIONS AND OTHER SOCIO-CULTURAL DATA BASES. - GASCHÉ, Jorge (2010)
This article proposes a classification for socio-cultural and linguistic data bases, especially those that document society, culture and language of Amazonian indigenous or rural mestizo people. The proposal was elaborated in the context of a DOBES language documentation project about the language use of the “People of the Center” (Bora, Witoto, Ocaina, Nonuya, and Resigaro). The basic principles of this proposal are derived from Bakhtin's/Vološinov's theory of the proposition.